The Assessment of Knowledge, Behaviors, and Anxiety Levels of the Orthodontists about COVID-19 Pandemic - (:unkn) unknown (AVES, 2020)
Objective: A new viral disease called Coronavirus disease-19 (COVID-19) affected the whole world because of its characteristics of spreading rapidly via respiratory droplets and aerosol. As one of the most aerosol-generating occupations, dentists are at high risk and are recommended to treat emergency cases only. We aimed to assess the general knowledge, emergencies, personal precautions, and avoided behaviors among the orthodontists and also their anxiety levels, during COVID-19. Methods: A survey research, including demographic information, general knowledge about COVID-19, treatment strategies, protective measures, and Generalized Anxiety Disorder (GAD) 7 test, was conducted via a web-based questionnaire (1 open-ended and 26 closed-ended questions). A total of 215 orthodontists older than 20 years of age and practicing in different regions of Turkey were included in this study. The answers received within the first 10 days were included. Results: Most of the orthodontists were aware of COVID-19 symptoms and transmission routes (n=159 and n=183, respectively). Almost all of them treated only emergency cases (n=209). Orthodontic emergencies were reported mostly as injury due to band/bracket failure, soft/hard tissue trauma, and problems in retention appliances (n=197, n=186, and n=81, respectively). The participants also avoided aerosol-generating procedures and used transmission-based protective equipment. The prevalence of GAD was 16.7% during COVID-19, and there was no statistically significant difference when it was stratified by gender, age, city, and COVID-19 related questions (p>0.05). Conclusion: The orthodontists followed the guidelines and took protective measures during COVID-19, and the majority had subthreshold anxiety levels.
Keywords: Anxiety; COVID-19; emergencies; orthodontists; personal protective equipment